On the Sobolev Dolbeault cohomology of a domain with pseudoconcave boundaries - Chen, Jian (Acta mathematica scientia, 2024)
In this note, we mainly make use of a method devised by Shaw [15] for studying Sobolev Dolbeault cohomologies of a pseudoconcave domain of the type Ω = Ω ˜ \ ∪ j = 1 m Ω j ¯ , where Ω ˜ and { Ω j } j = 1 m ⋐ Ω ~ are bounded pseudoconvex domains in ℂ n with smooth boundaries, and Ω ¯ 1 , ⋯ , Ω ¯ m are mutually disjoint. The main results can also be quickly obtained by virtue of [5].